Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/vnl.21397
|View full text |Cite
|
Sign up to set email alerts
|

The effect of crystallites on the rheological properties of microphase‐separated PVC‐PBA‐PVC triblock copolymers obtained by single electron transfer‐degenerative chain transfer living radical polymerization

Abstract: Linear and nonlinear rheological properties of poly(vinyl chloride) (PVC)-poly(n-butyl acrylate)-PVC triblocks of different compositions, obtained by single electron transfer-degenerative chain transfer living radical polymerization, are investigated, focusing on the effect of crystallites. Dynamic mechanical thermal analysis results show the existence of two glass transition temperatures, denoting microphase segregation. However, rather than phase separation, it is the presence of two types of crystals that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Poly(vinyl chloride) (PVC) and poly(vinyl chlorideco-butyl acrylate) (PVC-BA) and poly(vinyl chloride-co-2-ethylhexyl acrylate) (PVC-EHA) copolymers were obtained by single electron transfer-degenerative chain transfer living radical polymerization (SET-DCTLRP) as described elsewhere [14,15]. Additionally, reference plasticized PVC-DOP samples were obtained by melt mixing of the previously used PVC with the appropriate amounts of bis (2-ethylhexyl)phthalate (DOP).…”
Section: Experimental Part 21 Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Poly(vinyl chloride) (PVC) and poly(vinyl chlorideco-butyl acrylate) (PVC-BA) and poly(vinyl chloride-co-2-ethylhexyl acrylate) (PVC-EHA) copolymers were obtained by single electron transfer-degenerative chain transfer living radical polymerization (SET-DCTLRP) as described elsewhere [14,15]. Additionally, reference plasticized PVC-DOP samples were obtained by melt mixing of the previously used PVC with the appropriate amounts of bis (2-ethylhexyl)phthalate (DOP).…”
Section: Experimental Part 21 Materialsmentioning
confidence: 99%
“…The composition of the copolymers was evaluated by proton nuclear magnetic resonance ( 1 H-NMR) spectra recorded in a Bruker Analytische Messetechnik 500, at 500.13 MHz of resonance frequency. The band assignment was conducted following the criteria of our previous works [14,15], and the lines between 4 and 5 ppm (corresponding to -CO-O-CH 2 -) were used to calculate the composition of copolymers. Additionally, the microstructures of different copolymers were confirmed by 13 C-NMR, as it is explained in reference [15].…”
Section: Experimental Part 21 Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can cause a salubriousness problem, derived from the eventual migration of plasticizer, usually products related to phthalates family with different levels of toxicity . To face this challenge and reduce the T g of PVC, avoiding external plasticizers and procuring self‐plasticization, recently we showed that homogeneous random PVC–polybutyl acrylate (PBA) copolymers could be obtained by Single Electron Transfer–Degenerative Chain Transfer Living Radical Polymerization (SET–DTLRP) . This technique is a valuable synthetic alternative for PVC derivatives, as its controlled character permits the synthesis of well‐defined copolymers, from block to random structures, using diverse comonomers .…”
Section: Introductionmentioning
confidence: 99%